فعل الحجاج في بناء الخطاب عند طه عبدالرحمن: دراسة تطبيقية - مرمي، سهام; بن ميسي، زبيدة مونية (مؤسسة كنوز الحكمة للنشر والتوزيع, 2024)
إن السمة التي يتكوثر بها الخطاب هي صفته الحجاجية، لأن الخطاب في نظر طه عبد الرحمن موقوف على التعامل بين المتخاطبين بغية افتعال التأثير والإقناع في النفوس والعقول. وهذا ما تصبو إليه الصناعة الحجاجية من الخطاب، وهي صناعة متجانسة وخطابات الطاهائية طبيعياً مقارنة بالأسلوب الطاهائي المنشغل بالآليات اللغوية والمنطقية في بناء الأفهوم. وعلى هذا الأساس وردت هذه الدراسة، بهدف بيان المقصد من العلاقة بين الحجاج والخطاب، وبالتالي توضيح كيفية إنتاج خطاب من فعالية الحجاج، أي كيف يرتبط الاستدلال بالخطاب، ومن ثم تحديد الشروط التي ينبني عليها النص الاستدلالي بالخطاب حتى يحقق استمالة عقول المتلقين، والتي ستوضح ضمن القراءة الاستنتاجية لفلسفة الاختلاف. The characteristic that the discourse is multiplied by is its argumentative quality, because the discourse in the view of taha abd al-rahman is dependent on the interaction between the interlocutors in order to fabricate influence and persuasion in the souls and persuasion in the souls and minds. This what the pilgrimage industry is pouring into from the discourse. It is a homogeneous industry and tahai discourses naturally compared to the tahai style That Is preoccupied with linguistic and logical mechanisms in building the consept. On this basis, this study was presented, with the aim of clarifying the purpose of the relationship between the pilgrims and the discourse, and thus clarifying how to produce a discourse from the effectiveness of the pilgrims, that is, how the inference is related to the discourse, and then determining the condition upon which the inferential text is based on the discourse order to achieve the appeal of the minds the recipients, which will be clarified within the deductive reading for the philosophy of difference.
Keywords: اللغة العربية -- الخطاب الحجاجي -- الاستدلال الحجاجي -- الأفعال الكلامية -- عبدالرحمن، طه